FORMATIVE AND SUMMATIVE ASSESSMENT IN EDUCATION (International conference on multidisciplinary science, 2024)
Assessment plays a pivotal role in the teaching-learning process, providing valuable insights into students' progress and instructional efficacy. This article examines formative and summative assessment, highlighting their definitions, purposes, methods, and impacts on educational outcomes. It also explores how these assessment types complement each other to foster a comprehensive understanding of student achievement and growth.